Care, inequity and market. Concepts and experiences of maternity in women-mothers migrants’ domestic workers and middle and high class employer’s women in Buenos Aires. - Castilla, Vicky; Miguel, María Fernanda (Universidad Distrital Francisco José de Caldas, 2016)
Based on an ethnographic study this paper analyzes and describes the concepts and experiences of maternity in both women-mothers migrants who are domestic workers in the Metropolitan Buenos Aires area and the professionals working women who  employ them. We analyze the characteristics, tensions, conﬂicts  or correspondences that arise from the perspectives of  the mothers between the normative models of motherhood, affection and  experience of  care, attention and containment, considering the  differential logic that social and economic conditions printed  on them. We argue the existence of  a stratiﬁed reproduction in  which class, gender and nationality appear as distinguishing features of  the various maternity experiences, and however, they  share a common resolution of private care activities. For some  it is the commodiﬁcation and familiarization, for the others the  transnational networks of  care.